Determinants Of Digital Entrepreneurship Intention : Empirical Study of Senior High School Students in Bogor - Mulyana, Mumuh; Silalahi, Agung Sugianto; Riwoe, Febry Lodwyk Rihe (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This research discusses how entrepreneurial knowledge, income expectations, self-efficacy, and family environment can play a role and influence students' interest in entrepreneurship in online- based businesses, especially high school/vocational school students in the Bogor area. The aim of this research is to analyze and test the influence of entrepreneurial knowledge, income expectations, self-efficacy, and family environment in order to find out how big their influence is and how these three variables are able to influence the interest of high school/vocational school students in the Bogor area to become online entrepreneurs. In this study, 4 exogenous variables and 1 endogenous variable were used. The data collection method in this research used a questionnaire with a total of 1 7 9 respondents from SMA/SMK students in the Bogor area. For the data analysis method, use an analysis model with SEM-PLS or Structural Equation Modeling–Partial Least Square. To process the data using an analysis test tool, namely SmartPLS v. 3.2.9. The results of this research show that partially income expectations have a significant effect on interest in online entrepreneurship with a significance value of 0.002 < 0.05. Partially, self-efficacy has a significant effect on interest in online entrepreneurship with a significance value of 0.000 <0.05. And the family environment partially has a significant effect on interest in online entrepreneurship with a significance value of 0.000 <0.05. However, partially entrepreneurial knowledge does not significantly influence interest in online entrepreneurship with a significance value of 0.380 > 0.05. Keywords: entrepreneurship knowledge, income expectations, self-efficacy, family environment, interest in online entrepreneurship